Tamaraw resort hotel and aqua sports center : Puerto Galera, Oriental Mindoro - Deogracias, Reynan M. (Manila : National University, 2000)
This proposed tourist spot will be called "Tamaraw Rosert Hotel and Aqua Sports Center", whichb is named after the Organization "Tamaraw Group" which will undertake the financing and management of the proposed project.